(untitled) (Eurasian Journal of Learning and Academic Teaching, 2023)
The design of special-purpose clothing is a complex task, the solution of which requires an integrated approach that takes into account the increased requirements for the operational characteristics of manufactured clothing, as well as the results of a comprehensive analysis of the current requirements of potential consumers, which are associated with the peculiarities of their professional activities and high risks of their life safety arising when performing military women’s official tasks.